Morphology and molecular phylogeny reveal two new species in Russula sect. Ingratae from China - Chen, Bin; Song, Jie; Zhang, Jin-Hua; Liang, Jun-Feng (Phytotaxa, 2021)
Two new species of Russula are described and illustrated in this paper. Russula clavulus is recognised by a pale yellow pileus centre, white margin with tuberculate striation, white to pale lamellae with small pale yellow spots, white to light yellow spore print, subglobose to broadly ellipsoid spores with short or long ridges and hymenial cystidia on lamellae sides that are mainly subclavate or fusiform. Russula multilamellula is morphologically characterised by the brownish orange to hazel pileus centre and satin white to yellowish-white margin with brownish tinge, lamellulae that are usually irregular in length and often anastomosing with lamellae, subglobose to broadly ellipsoid spores with short or long ridges and clavate hymenial cystidia. The combination of morphological features and multigene phylogenetic analyses of ITS-nrLSU-RPB2-mtSSU data indicated that these two new taxa belong to Russula subg. Heterophyllidia sect. Ingratae.